Comparison the Amount of Calcium and Phosphor in Saliva of Postmenopausal Women with and Without Osteoporosis - Leila Aliyari; Arezou Hatami Khanghahi (Mashhad University of Medical Sciences, 2024)
Background: Osteoporosis continues to be a significant clinical issue worldwide, especially for postmenopausal women. Early diagnosis can play a key role in preventing fractures and further complications. Salivary diagnostic testing methods have gained popularity due to their low cost and accessibility. This study aimed to investigate the values of salivary calcium and phosphorus biomarkers for screening postmenopausal women in terms of osteoporosis development.Methods and Materials: This case-control study included postmenopausal women with at least 45 years of age who admitted to Payambaran Hospital, Tehran, Iran to undergo bone densitometry. Participants were divided to case and control groups based on the bone densitometry results. . Bone density was measured usingdual energy X-ray absorptiometry (DEXA) scans.  The case group consisted of women with osteoporosis and the control group included healthy individuals. Unstimulated saliva samples were collected to measure the salivary calcium and phosphorus biomarkers. Independent samples T-test was employed for inter-group comparisons. Rock curve was used to calculate the cut-off point, sensitivity, and specificity, positive and negative predictive value of the variables. P-value less than 0.05 was considered statistically significant.Results: A total of 70 patients, 38 in the control group and 32 in the case group, completed the study.The average salivary calcium levels were significantly higher in patients with osteoporosis compared to healthy individuals (P=0.01). However, regarding the salivary phosphorus levels, there was no statically significant difference between the two study groups (P=0.44). According to the Rock curve, the diagnostic value was not favorable for any of the biomarkers.Conclusion: Our findings suggest that evaluating the salivary calcium concentrations with an appropriate cut-off point value can possibly serve as an appropriate method for screening osteoporosis in postmenopausal women.